Dynamic physical education for elementary school children - Pangrazi, Robert P.; Beighle, Arizona Aaron (San Francisco : Benjamin Cummings, 2004)
Provides the combination of theoretical framework and hands-on activities. This fourteenth edition offers information on trends, research, and fitness technology. It guides new teachers with techniques and covers games and activities suitable for developmental level to teaching strategies and guidelines.
Includes bibliographical references and indexes.
Keywords: Physical education and training -- Curricula -- United States; Physical education and training -- Study and teaching (Elementary) -- United States; Physical education and training -- Curricula -- Canada; Physical education and training -- Study and teaching (Elementary) -- Canada